2012
DOI: 10.1103/physrevb.85.245105
|View full text |Cite
|
Sign up to set email alerts
|

Electron pairing and Coulomb repulsion in one-dimensional anharmonic lattices

Abstract: We show that in anharmonic one-dimensional crystal lattices pairing of electrons or holes in a localized bisolectron state is possible due to coupling between the charges and the lattice deformation that can overcompensate the Coulomb repulsion. Such localized soliton-like states appear as traveling ground bound singlet states of two extra electrons in the potential well created by the local lattice deformation. We also find the first excited localized state of two electrons in a soliton-like lattice deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…can be approximated near the minimum with high degree of precision by the anharmonic potential U c (see (12.42)) (for more details see [5]). …”
Section: Comparison With Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…can be approximated near the minimum with high degree of precision by the anharmonic potential U c (see (12.42)) (for more details see [5]). …”
Section: Comparison With Numerical Simulationsmentioning
confidence: 99%
“…In view of the above here we explicitly analyze how the lattice anharmonicity added to the electron-phonon interaction facilitates electron pairing in a one-dimensional lattice and also helps overcoming Coulomb repulsion. It has been shown that anharmonic lattices also favor pairing of electrons (holes) in a singlet localized state [5,44,45]. While in harmonic lattices the nonlinearity in the system is due to the electron-lattice interaction, in anharmonic lattices there are two nonlinearities: the nonlinearity of the lattice itself, and the electron-lattice interaction.…”
Section: Introductionmentioning
confidence: 98%
“…A generalization of the polaron to solectron, which is the bound state of the crowdion or DB and electron has been proposed () to discuss the peculiarities of electron transport in crystals .…”
Section: Possible Applications Of Discrete Breathersmentioning
confidence: 99%
“…To calculate it, let us consider, for simplicity, the case of a bisolectron at rest, V = 0. Substituting function (64) (or (65) ) and the corresponding lattice deformation (30) into the Hamiltonian H and expanding the result with respect to l in the assumption l < µ = 2π/κ ν , we obtain, after the integration, the total energy of the system including the Coulomb repulsion (62):…”
Section: Bisolectron With Account Of the Coulomb Repulsionmentioning
confidence: 99%